Mouse laser injury models: variations on a theme - Timothy J. Stalker (Platelets, 2020)
A confluence of technological advances in genetic manipulation and molecular-based fluorescence imaging has led to the widespread adoption of laser injury models to study hemostasis and thrombosis in mice. In all animal models of hemostasis and thrombosis, detailing the nature of experimentally induced vascular injury is paramount in enabling appropriate interpretation of experimental results. A careful appraisal of the literature shows that direct laser-induced injury can result in variable degrees of vascular damage. This review will compare and contrast models of laser injury utilized in the field, with an emphasis on the mechanism and extent of injury, the use of laser injury in different vascular beds and the molecular mechanisms regulating the response to injury. All of these topics will be discussed in the context of how distinct applications of laser injury models may be viewed as representing thrombosis and/or hemostasis.